2009
DOI: 10.1007/s10194-009-0178-3
|View full text |Cite
|
Sign up to set email alerts
|

Headache patients in the emergency department of a Greek tertiary care hospital

Abstract: The aim of this study was to record the demographic and epidemiological data on adult patients with headache who attend the emergency department (ED) and the diagnoses that made by the neurologists in the ED of a tertiary care hospital in metropolitan Thessaloniki (Greece). In an open prospective study, demographic and epidemiological data were collected on all patients who reported headache (as chief complaint or not) and presented to the ED of Papageorgiou Hospital between August 2007 and July 2008. Headache… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
15
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 22 publications
6
15
0
Order By: Relevance
“…The strong association between dyspnoea and hospitalisation and acute morbidity in our study is in line with another study, in which 59% of patients presenting to the ED with dyspnoea were admitted . On the other hand, the low prevalence of acute morbidity in patients with complaints such as chest pain, headache or dizziness is in line with previous studies . About half of the patients presenting with abdominal pain suffered from acute morbidity in our study, which is in line with previous reports .…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The strong association between dyspnoea and hospitalisation and acute morbidity in our study is in line with another study, in which 59% of patients presenting to the ED with dyspnoea were admitted . On the other hand, the low prevalence of acute morbidity in patients with complaints such as chest pain, headache or dizziness is in line with previous studies . About half of the patients presenting with abdominal pain suffered from acute morbidity in our study, which is in line with previous reports .…”
Section: Discussionsupporting
confidence: 93%
“…On the other hand, the low prevalence of acute morbidity in patients with complaints such as chest pain, headache or dizziness is in line with previous studies 4, 22, 23, 24. About half of the patients presenting with abdominal pain suffered from acute morbidity in our study, which is in line with previous reports 5, 25, 26.…”
Section: Discussionsupporting
confidence: 93%
“…However, other studies from emergency departments and general practice patients revealed higher percentage of secondary headaches ranging from 22.1% to 42% [4], [15], [18], [19]. We speculated that the reason is that physicians from both neurological and emergency department outpatient are trained to recognize headache disorders as diseases that were attributed to some somatic reasons.…”
Section: Discussionmentioning
confidence: 88%
“…Thus, headache patients visiting clinic may show different clinical features and types from those obtained from the general population-based studies. TTH was reported to be the most frequent diagnosis, followed by secondary headache and migraine in the emergent department based on a Greek study [4]. However, in a Hungary study, migraine was the most common headache, while TTH patients reported more severe disability [5].…”
Section: Introductionmentioning
confidence: 98%
“…Patients who consult doctors have different clinical features and the distribution of headache types seen in the clinic differs from population-based studies. A study by an ED in Greece [ 3 ] reported that TTH was the most frequent diagnosis, followed by secondary headache and migraine. In a clinical study from a headache center in east Hungary [ 4 ], migraine was the most common headache, while TTH patients reported more severe disability than migraines.…”
Section: Introductionmentioning
confidence: 99%